Dependence of the effective surface tension of liquid phase eutectic gallium indium on wrinkles of the surface oxide. (October 2021) - Lee, Jongwon; Jung, Sangyun; Kim, Wonjung
Abstract: We investigated the effective surface tension of liquid eutectic gallium indium (EGaIn) with oxide skin. Our visualization of the EGaIn interface during extension and compression indicated the compression causes the wrinkles on the oxide skin, which is then partially smoothed out by extension. We found that the creation of the interface was the combined result of tearing of the oxide skin and the unfolding of oxide wrinkles. Our experiments revealed that the effective surface tension depends on oxide wrinkle, and the value is 0.7 N/m in the absence of wrinkles, but can be as small as ∼ 0.5 N/m in the presence of surface wrinkles.